SARS-CoV-2 Coronavirus Spike Protein-Induced Apoptosis, Inflammatory, and Oxidative Stress Responses in THP-1-Like-Macrophages: Potential Role of Angiotensin-Converting Enzyme Inhibitor (Perindopril) - Barhoumi, Tlili; Alghanem, Bandar; Shaibah, Hayat; Mansour, Fatmah A.; Alamri, Hassan S.; Akiel, Maaged A.; Alroqi, Fayhan; Boudjelal, Mohammad (Frontiers in Immunology, 2021)
A purified spike (S) glycoprotein for SARS-COV-2 coronavirus was used to studying its effects on THP-1 macrophages, PBMCs and HUVEC cells. The S protein mediates SARS-CoV-2 entry into cells through binding to angiotensin converting enzyme 2 (ACE2) receptors. We measured viability, intracellular cytokines release, oxidative stress, pro-inflammatory markers and THP-1-like macrophage polarization. We identified an increase in apoptosis, ROS generation, MCP-1 and intracellular calcium expression in THP-1 macrophages. Furthermore, stimulation with the S protein polarizes THP-1 macrophages towards pro-inflammatory futures with an increase in TNFα and MHC-II M1-like phenotype markers. Treatment of cells with an ACE inhibitor, perindopril at 100µM reduced apoptosis, ROS and MHC-II expression. We further analyzed the sensitivity of HUVEC cells after exposure to a conditioned media (CM) of THP-1 macrophages stimulated with S protein. CM induced endothelial cell apoptosis and MCP-1 expression. Treatment with perindopril reduced these effects. However, direct stimulation of HUVEC cells with S protein slightly increased HIF1α and MCP-1 expression which was significantly exaggerated by ACE inhibitor treatment. S protein stimulation induced ROS generation and changed mitogenic responses of PBMCs through upregulation of TNFα and IL-17 cytokine expressions. These effects were blunted by perindopril (100µM) treatment. Proteomic analysis of S protein stimulated THP-1 macrophages with or without perindopril (100µM) uncovered more than 400 differentially regulated proteins. Our results provide a mechanistic analysis suggesting that blood and vascular component could be activated directly through S protein systemically present in circulation and that activation of local renin angiotensin system might be partially involved in this process.